Preparation and application of zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer
By introducing zwitterionic polymer monomer into hydrophobic acrylate polymer, a polymer with excellent optical and structural properties, strong hydrophilicity, strong protein adsorption ability and no cytotoxicity was prepared, and IOL material was solved. The problems caused by PCO after intraocular implantation significantly improve the biocompatibility of the material and the ability to resist protein adsorption.
Patent Information
- Application Number
- CN202411590586.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
AI Technical Summary
Existing intraocular lens (IOL) materials are prone to cause posterior capsule turbidity (PCO) after implantation into the eyes. This is mainly due to the interaction between non-specific proteins and materials and cells, which lead to cell adhesion, migration and proliferation, affecting the material's Biocompatibility.
By introducing zwitterionic polymer monomers into hydrophobic acrylate polymers, a polymer with excellent optical and structural properties, strong hydrophilicity, strong protein adsorption ability and no cytotoxicity was prepared and applied to Material for artificial intraocular lens preparation.
The glass transition temperature of this material is lower than 25 °C, and the light transmittance exceeds 90% in the visible light range. It also has high relative cellular activity and biocompatibility, which significantly reduces the adsorption content of the surface of the material and reduces IOL transplantation. Probability of PCO after entry.
Smart Images

Figure CN119391032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic chemistry, and in particular to the preparation and application of a zwitterionic polymer monomer-modified soft hydrophobic acrylate copolymer. Background Art
[0002] Cataract is a disease caused by lens metabolism disorder due to aging, heredity, radiation and other reasons, resulting in denaturation and turbidity of lens protein. At present, the only effective means to treat cataracts is surgical replacement of artificial lens (IOL). However, as a medical material, IOL will react with foreign bodies when implanted in the eye, resulting in various postoperative complications. Among them, posterior capsule opacification (PCO) is the most common and serious complication. Therefore, researchers often use methods such as designing IOL shape and improving surgical operation methods to prevent and stop the formation of PCO. Chinese patent CN103099705A discloses a device for preventing and treating PCO, which can selectively remove lens epithelial cells and prevent PCO. However, it still has the defect of not being able to completely remove excess epithelial cells on the inner capsule of the lens. With the progress of research, researchers have found that non-specific proteins will cause cells and biomaterials to interact with each other, further leading to cell adhesion, migration and proliferation, and ultimately leading to tissue regeneration, affecting the biocompatibility of the material. Therefore, to reduce the incidence of PCO, the surface of the IOL material can be modified to improve the material's ability to resist protein adhesion and enhance biocompatibility. Summary of the invention
[0003] The purpose of the present invention is to solve the above-mentioned problems in the prior art and provide a preparation and application of a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer. By introducing a zwitterionic polymer monomer into the hydrophobic acrylate polymer, a polymer with excellent optical and structural properties, strong hydrophilicity, strong anti-protein adsorption ability and no cytotoxicity is prepared, and the polymer is applied to the preparation of artificial intraocular lens materials.
[0004] In order to achieve the above object, the present invention adopts the following technical scheme:
[0005] A method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer comprises the following steps:
[0006] 1) Mixing the first monomer, the second monomer, the crosslinking agent and the initiator and stirring until the solution is clear to obtain a mixed solution 1;
[0007] 2) Degassing the mixed solution 1, and then performing two-stage heating polymerization, and finally washing and drying the obtained sample to obtain a base material;
[0008] 3) mixing benzophenone, 1,4-butanediol diacrylate, additives, and auxiliary additives in anhydrous ethanol to obtain a mixed solution 2;
[0009] 4) adding the mixed solution 2 dropwise to the base material until the base material is completely immersed; then irradiating the surface of the base material with ultraviolet light, and finally rinsing and drying to obtain the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer.
[0010] The first monomer comprises at least one of phenylethyl acrylate, benzyl acrylate, benzyl methacrylate, phenylethyl methacrylate, phenylpropyl acrylate, and phenylpropyl methacrylate; preferably phenylethyl acrylate, benzyl acrylate, and benzyl methacrylate;
[0011] The second monomer includes at least one of methoxyethyl methacrylate, ethoxyethyl methacrylate, propoxyethyl methacrylate, butoxyethyl methacrylate, and pentoxyethyl methacrylate; preferably ethoxyethyl methacrylate, propoxyethyl methacrylate, and pentoxyethyl methacrylate;
[0012] The additive includes at least one of sulfobetaine methacrylate and carboxybetaine methacrylate;
[0013] The auxiliary additive includes at least one of hydroxyethyl methacrylate, ethyl acrylate, propyl acrylate, hydroxypropyl methacrylate, propyl methacrylate, and butyl methacrylate; preferably ethyl acrylate, hydroxypropyl methacrylate, and propyl methacrylate;
[0014] The crosslinking agent is 1,4-butanediol diacrylate.
[0015] The initiator is bis(4-tert-butylcyclohexyl)peroxydicarbonate.
[0016] The weight proportions of the components in step 1) are as follows: 50-90 parts of the first monomer, 5-50 parts of the second monomer, 2-10 parts of the crosslinking agent, and 0.5-5 parts of the initiator. Preferably, 74-84 parts of the first monomer, 15-25 parts of the second monomer, 3-7 parts of the crosslinking agent, and 1-3 parts of the initiator.
[0017] In step 2), the degassing time is 1 to 10 h, preferably 2 to 4 h; the specific conditions of the two-stage heating polymerization are that the temperature of the first stage is 50 to 100 °C, and the reaction time is 5 to 25 h; the temperature of the second stage is 100 to 150 °C, and the reaction time is 2 to 12 h. Preferably, the temperature of the first stage is 50 to 60 °C, and the reaction time is 10 to 15 h; the temperature of the second stage is 105 to 115 °C, and the reaction time is 8 to 12 h.
[0018] The weight parts of each component in step 3) are as follows: additives are not more than 80 parts, auxiliary additives are not more than 40 parts, benzophenone is not more than 30 parts, and 1,4-butanediol diacrylate is not more than 30 parts. Preferably, additives are not more than 60-70 parts, auxiliary additives are 10-20 parts, benzophenone is 5-15 parts, and 1,4-butanediol diacrylate is 5-15 parts.
[0019] In step 4), the wavelength of the ultraviolet light is 100-600 nm, and the irradiation time is no longer than 10 min; preferably, the wavelength of the ultraviolet light is 350-450 nm, and the irradiation time is 1-4 min.
[0020] The zwitterionic polymer monomer-modified soft hydrophobic acrylate copolymer of the present invention is used for preparing materials for artificial intraocular lenses.
[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0022] The copolymer prepared by the present invention has a glass transition temperature lower than 25°C, a transmittance of more than 90% in the visible light range, and a high relative cell activity, improved biocompatibility, and anti-protein adhesion ability, which greatly reduces the protein adsorption content on the surface of the material. The material of the present invention is used to prepare intraocular lenses, which can reduce protein adsorption to a certain extent and reduce the probability of PCO after IOL implantation in the eye. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : is a surface water contact angle diagram of the obtained copolymer material; wherein a is the surface water contact angle of the copolymer obtained in Comparative Example 2, b is the surface water contact angle of the copolymer obtained in Comparative Example 1, c is the surface water contact angle of the copolymer obtained in Example 3, d is the surface water contact angle of the copolymer obtained in Example 1, e is the surface water contact angle of the copolymer obtained in Example 6, and f is the surface water contact angle of the copolymer obtained in Example 5;
[0024] Figure 2 is the light transmittance diagram of Example 1;
[0025] Figure 3 : is the BSA adsorption graph of the obtained copolymer material: wherein, a is the TCPS blank control group without adding materials, b is the BSA adsorption content on the surface of the copolymer material obtained in Comparative Example 2, c is the BSA adsorption content on the surface of the copolymer material obtained in Comparative Example 1, d is the BSA adsorption content on the surface of the copolymer material obtained in Example 3, e is the BSA adsorption content on the surface of the copolymer material obtained in Example 1, f is the BSA adsorption content on the surface of the copolymer material obtained in Example 6, and g is the BSA adsorption content on the surface of the copolymer material obtained in Example 5. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0027] Example 1
[0028] (1) 0.97 g of phenethyl acrylate, 0.97 g of phenethyl methacrylate, 0.52 g of ethoxyethyl methacrylate, 0.10 g of 1,4-butanediol diacrylate, and 0.039 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate were placed in a beaker and stirred until the solution became clear, thereby preparing a mixed solution 1;
[0029] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0030] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0031] (4) Weigh 0.17 g of sulfobetaine methacrylate, 0.04 g of hydroxyethyl methacrylate, 0.03 g of benzophenone and 0.03 g of 1,4-butanediol diacrylate in 13 mL of anhydrous ethanol and ultrasonically treat to prepare a mixed solution 2;
[0032] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0033] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0034] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0035] Example 2
[0036] (1) Place 1.48 g of phenethyl acrylate, 1.48 g of phenethyl methacrylate, 0.80 g of ethoxyethyl methacrylate, 0.12 g of 1,4-butanediol diacrylate, and 0.12 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate in a beaker and stir until the solution becomes clear to prepare a mixed solution 1;
[0037] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0038] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0039] (4) Weigh 0.25 g of sulfobetaine methacrylate, 0.11 g of hydroxyethyl methacrylate, 0.02 g of benzophenone and 0.02 g of 1,4-butanediol diacrylate in 20 mL of anhydrous ethanol and ultrasonically treat to prepare a mixed solution 2;
[0040] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0041] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0042] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0043] Example 3
[0044] (1) Place 3.4 g of phenethyl acrylate, 3.4 g of phenethyl methacrylate, 1.8 g of ethoxyethyl methacrylate, 0.36 g of 1,4-butanediol diacrylate, and 0.14 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate in a beaker and stir until the solution becomes clear to prepare a mixed solution 1;
[0045] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0046] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0047] (4) Weigh 0.63 g of sulfobetaine methacrylate, 0.09 g of hydroxyethyl methacrylate, 0.09 g of benzophenone and 0.09 g of 1,4-butanediol diacrylate, add them to 45 mL of anhydrous ethanol, and ultrasonically treat them to prepare a mixed solution 2;
[0048] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0049] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0050] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0051] Example 4
[0052] (1) Place 4.0 g of phenethyl acrylate, 4.0 g of phenethyl methacrylate, 1.0 g of ethoxyethyl methacrylate, 0.50 g of 1,4-butanediol diacrylate, and 0.50 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate in a beaker and stir until the solution becomes clear to prepare a mixed solution 1;
[0053] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0054] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0055] (4) Weigh 0.60 g of sulfobetaine methacrylate, 0.20 g of hydroxyethyl methacrylate, 0.10 g of benzophenone and 0.10 g of 1,4-butanediol diacrylate in 5 mL of anhydrous ethanol and ultrasonically treat to prepare a mixed solution 2;
[0056] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0057] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0058] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0059] Example 5
[0060] (1) Place 4.8 g of phenethyl acrylate, 4.8 g of phenethyl methacrylate, 2.6 g of ethoxyethyl methacrylate, 0.52 g of 1,4-butanediol diacrylate, and 0.20 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate in a beaker and stir until the solution becomes clear to prepare a mixed solution 1;
[0061] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0062] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0063] (4) Weigh 0.72 g of sulfobetaine methacrylate, 0.33 g of hydroxyethyl methacrylate, 0.13 g of benzophenone and 0.13 g of 1,4-butanediol diacrylate, add them together in 65 mL of anhydrous ethanol, and ultrasonically treat to prepare a mixed solution 2;
[0064] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0065] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0066] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0067] Example 6
[0068] (1) 0.45 g of phenethyl acrylate, 0.45 g of phenethyl methacrylate, 0.24 g of ethoxyethyl methacrylate, 0.048 g of 1,4-butanediol diacrylate, and 0.018 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate were placed in a beaker and stirred until the solution became clear, thereby preparing a mixed solution 1;
[0069] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0070] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, wash the remaining raw materials with anhydrous ethanol, and then put the sample into a vacuum drying oven at 60 °C for 24 h to obtain the base material;
[0071] (4) Weigh 0.07 g of sulfobetaine methacrylate, 0.02 g of hydroxyethyl methacrylate, 0.01 g of benzophenone and 0.01 g of 1,4-butanediol diacrylate, add them together in 6 mL of anhydrous ethanol, and ultrasonically treat them to prepare a mixed solution 2;
[0072] (5) Prepare the base material into a circular sheet, place it in a mold, and add the mixed solution 2 dropwise with a dropper until the base material is completely immersed;
[0073] (6) Irradiate the material surface with ultraviolet light of wavelength 365 nm for 3 min;
[0074] (7) The material was taken out, rinsed with deionized water to remove the residual raw materials on the surface of the material, and then placed in a 60° C. oven for drying for 2 h to prepare the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer material.
[0075] Comparative Example 1
[0076] (1) 0.97 g of phenethyl acrylate, 0.97 g of phenethyl methacrylate, 0.52 g of ethoxyethyl methacrylate, 0.10 g of 1,4-butanediol diacrylate, and 0.039 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate were placed in a beaker and stirred until the solution became clear, thereby preparing a mixed solution 1;
[0077] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0078] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 60 °C vacuum drying oven for vacuum drying for 24 h to obtain the base material.
[0079] Comparative Example 2
[0080] (1) Place 0.97 g of phenethyl acrylate, 0.97 g of phenethyl methacrylate, 0.10 g of 1,4-butanediol diacrylate, and 0.039 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate in a beaker and stir until the solution becomes clear to prepare a mixed solution 1;
[0081] (2) Place the mixed solution 1 in a vacuum drying oven for degassing for 2 h, add it dropwise into the mold, transfer it to a 60 °C oven for polymerization reaction for 14 h, and then place it in a 110 °C oven for polymerization reaction for 8 h;
[0082] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 60 °C vacuum drying oven for vacuum drying for 24 h to obtain the base material.
[0083] The contact angle, optical properties, protein adsorption capacity, and cytotoxicity of the copolymer materials provided in Examples 1 to 6 and Comparative Examples 1 and 2 were tested according to the following method.
[0084] Contact angle test
[0085] Specific method: In order to evaluate the wettability of the material surface, a contact angle meter (SPCAX3, Beijing HARKE Company, Beijing) was used to measure the water contact angle of the materials of Examples 1, 3, 5, and 6. The test was carried out at room temperature, and each test was set to deposit a drop of water (2.0 µL) on the sample surface. Five different areas of each sample were taken for the test experiment, and the average value was taken.
[0086] Figure 1 This is a water contact angle diagram of the surface of the copolymer material of Example 1. From the analysis of the diagram, it can be obtained that, compared with Comparative Examples 1 and 2 without surface modification, the surface water contact angle of the embodiment is significantly reduced, and the hydrophilicity is improved; and, the surface water contact angle of the copolymer material of Example 1 is the smallest, and it has the best hydrophilicity, which improves the compatibility of the material in the eye.
[0087] Transmittance measurement experiment
[0088] Specific method: The transmittance of the copolymer material was measured using a SHIMADZU UV-1780 UV-visible spectrophotometer. First, the material was cut into long thin strips of 1×3×0.04 cm in size and placed in a cuvette filled with physiological saline. The test mode was selected as transmittance, and the scanning wavelength range was 200~800 nm. The data showed that the transmittance was greater than 90% in the visible light range of 400~800 nm, and the optical performance was good.
[0089] Figure 2 The transmittance measurement diagram of the copolymer material in Example 1 is shown in the figure. From the analysis of the figure, it can be found that in the visible light range (800-400 nm), the transmittance of the copolymer material in Example 1 is greater than 90%. In addition, its transmittance drops rapidly in the ultraviolet range (400-200 nm), and the transmittance of the material drops to 0 in the UV-C range (280-200 nm), which protects the retina from ultraviolet radiation damage to a certain extent.
[0090] Protein adsorption assay experiments
[0091] Specific method: In order to analyze the anti-protein adsorption ability of the material, the protein adsorption performance of the material surface was measured by the BCA method. The material was cut into a circular thin sheet sample with a diameter of 5 mm and co-cultured with 0.2 mL of 2 mg / mL BSA working solution in a 96-well plate for 3 h. The material was taken out and rinsed with PBS buffer 6 times. After removing the protein deposited on the surface of the material, it was analyzed in a 96-well plate with 0.2 mL of 1 wt% SDS solution at 37 °C for 4 h. The BCA working solution was mixed with the analytical solution and stained for 30 min at 37 °C in a 96-well plate. The absorbance of the staining solution at 562 nm was measured using an enzyme reader, and tissue culture polystyrene (TCPS) was used as the control group.
[0092] Figure 3 : is the BSA adsorption diagram of the copolymer material surface of Example 1. Analysis of the diagram shows that, compared with Comparative Examples 1, 2 and other examples, the copolymer material surface of Example 1 has the least BSA adsorption content and the best anti-protein adsorption ability.
[0093] Cytotoxicity assay
[0094] Specific methods: In order to explore the biological properties of the material, the CCK-8 method was used to study the cytotoxicity of the material. First, HaCaT cells were cultured in DMEM medium, 10 wt% fetal bovine serum was added, and the cells were cultured at 37 °C in a 5% CO2 incubator until the HaCaT cells covered a 6 cm diameter culture dish. Secondly, 0.25% trypsin-0.02% EDTA was used to digest the fused cells, and then centrifuged at 1000 rpm for 3 min to collect the cells. Then, 2 mL of DMEM was used to resuspend and prepare cell solution. Then, 0.15 mL of cell solution was aspirated and placed in 10 mL of DMEM medium to mix and prepare inoculation solution. 0.2 mL of inoculation solution was aspirated and inoculated into a 96-well plate and cultured in a 5% CO2 incubator at 37 °C for 24 h. The copolymer material was cut into 6 circular slices with a diameter of 5 mm and added to a 96-well plate to co-culture with cells for 24 h. Finally, the original culture medium was removed, the cells were rinsed twice with PBS, and the culture medium in the 96-well plate was replaced with 100 µL CCK-8 solution. After culturing in the incubator for 2 h, the liquid was aspirated into the 96-well plate and its absorbance at 450 nm was measured using an ELISA reader.
[0095] Compared with the relative cell survival rate of 96.93% in comparative example 1 and 97.87% in comparative example 2, the relative cell survival rate of the copolymer material of Example 1 after surface modification was higher, reaching 99.14%. After HaCaT cells were co-cultured with it for 24 h, the relative cell survival rate exceeded 99%, and the biocompatibility was improved.
[0096] The materials of the present invention mainly include hydrophilic polymers and zwitterionic polymers. Both are electrically neutral, which can reduce electrostatic interactions with proteins, and both have excellent hydrophilicity and interact with water molecules. The above two properties work together to effectively resist the nonspecific adsorption of proteins, and are extremely suitable for surface modification of IOL materials to improve the material's ability to resist protein adhesion.
Claims
1. A method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer, characterized in that: The following steps are involved: 1) Mixing the first monomer, the second monomer, the crosslinking agent and the initiator and stirring until the solution is clear to obtain a mixed solution 1; 2) Degassing the mixed solution 1, and then performing two-stage heating polymerization, and finally washing and drying the obtained sample to obtain a base material; 3) mixing benzophenone, 1,4-butanediol diacrylate, additives, and auxiliary additives in anhydrous ethanol to obtain a mixed solution 2; 4) adding the mixed solution 2 dropwise to the substrate material until the substrate material is completely immersed; then irradiating the surface of the substrate material with ultraviolet light, and finally rinsing and drying to obtain the zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer; The first monomer includes at least one of phenylethyl acrylate, benzyl acrylate, benzyl methacrylate, phenylethyl methacrylate, phenylpropyl acrylate, and phenylpropyl methacrylate; the second monomer includes at least one of methoxyethyl methacrylate, ethoxyethyl methacrylate, propoxyethyl methacrylate, butoxyethyl methacrylate, and pentyloxyethyl methacrylate; the additive includes at least one of sulfobetaine methacrylate and carboxybetaine methacrylate; the auxiliary additive includes at least one of hydroxyethyl methacrylate, ethyl acrylate, propyl acrylate, hydroxypropyl methacrylate, propyl methacrylate, and butyl methacrylate.
2. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: The crosslinking agent is 1,4-butanediol diacrylate.
3. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: The initiator is bis(4-tert-butylcyclohexyl)peroxydicarbonate.
4. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: The weight parts of the components in step 1) are as follows: 50-90 parts of the first monomer, 5-50 parts of the second monomer, 2-10 parts of the crosslinking agent, and 0.5-5 parts of the initiator.
5. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: In step 2), the degassing time is 1 to 10 h; the specific conditions of the two-stage heating polymerization are that the temperature of the first stage is 50 to 100 °C, and the reaction time is 5 to 25 h; the temperature of the second stage is 100 to 150 °C, and the reaction time is 2 to 12 h.
6. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: The weight proportions of the components in step 3) are as follows: additives not exceeding 80 parts, auxiliary additives not exceeding 40 parts, benzophenone not exceeding 30 parts, and 1,4-butanediol diacrylate not exceeding 30 parts.
7. The method for preparing a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 1, characterized in that: In step 4), the wavelength of ultraviolet light is 100-600 nm; and the irradiation time is no longer than 10 min.
8. A zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
9. The use of a zwitterionic polymer monomer modified soft hydrophobic acrylate copolymer according to claim 8, characterized in that: Used in the preparation of artificial intraocular lenses.
Citation Information
Patent Citations
Device for preventing and treating posterior capsule opacification
CN103099705A